The development of thai pre-service mathematics teachers' pedagogical content knowledge: A series teaching case - Tongta Somchaipeng (2018)
One important component of pedagogical content knowledge (PCK) is knowledge of strategies and representations for teaching particular topics. Aimed to enhance this component of pre-service mathematics teachers, the abstract and symbolic concept of series is used as a learning context of a learning unit which is called "PCK+series unit", which was developed. The teaching and learning process of this unit was based on the constructivist approach to foster atmospheres of mathematics learning through key features of a constructivist view of learning, and was implemented while enhancing pre-service teachers' PCK in instructional designs and teaching of series. The unit was implemented (8 weeks) with 23 pre-service mathematics teachers in the third year of attending selected topics in a mathematics instruction course. The collection of data involved a pre-post questionnaire, weekly journals, and video recording of series lesson plan presentation sessions with their respective mentors. At the beginning of the PCK+series unit implementation, most pre-service teachers were unable to employ appropriate teaching strategies required to explain series concepts. Most of them planned to teach by showing various series formulas and giving some examples of problem solving through a traditional teaching approach. After the implementation, learning components of PCK and several activities including brief hands-on activities helped pre-service teachers to realize that moving from the constructivist learning theory into classroom practice is necessary for their future students. The results support a growing awareness among pre-service teachers concerning the need to understand students' prior knowledge and relate it with new learning experiences provided in teaching and learning situation; for example using guided questions and designing series models to help students comprehend and build series' formulas from their own ideas. © Common Ground, Tongta Somchaipeng, Tussatrin Kruatong.